Area deprivation and age related macular degeneration in the EPIC-Norfolk Eye Study - Yip, Jennifer L.Y. (Public Health, 2015)
OBJECTIVES: To investigate the relationship between area deprivation, individual socio-economic status (SES) and age related macular degeneration (AMD). STUDY DESIGN: Cross sectional study nested within a longitudinal cohort study. METHODS: Data were collected in the EPIC-Norfolk Eye Study by trained nurses, using standardized protocols and lifestyle questionnaires. The English Index of multiple deprivation 2010 (IMD) was derived from participants' postcodes. AMD was identified from standardized grading of fundus photographs. Logistic regression was used to examine associations between IMD, SES and AMD. RESULTS: 5344 pairs (62.0% of total 8623) of fundus photographs were of sufficient quality for grading of AMD. Of 5182 participants with complete data, AMD was identified in 653 participants (12.60%, 95%CI = 11.7–13.5%). Multivariable logistic regression showed that people living in the most affluent 5% of areas had nearly half the odds of AMD compared to those living in comparatively more deprived areas (OR = 0.56, 95% CI = 0.36–0.89, P = 0.02), after adjusting for age, sex, education, social class and smoking. CONCLUSIONS: The authors found that living in the most affluent areas exerted a protective effect on AMD, independently of education and social class. Further investigation into underlying mechanisms will inform potential interventions to reduce health inequalities relating to AMD.